Pedro García Ruiz - Experimental and Simulated Study of Ammonia Combustion at High Pressures - García-Ruiz, Pedro (Jornada de Jóvenes Investigadores del I3A, 2022)
Experimental and Simulated Study of Ammonia Combustion at High Pressures